2022
DOI: 10.3390/ph15030280
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Molecular Docking, and Biological Evaluation of Pyrazole Hybrid Chalcone Conjugates as Potential Anticancer Agents and Tubulin Polymerization Inhibitors

Abstract: Some (E)-3-(3-(4-(benzyloxy)phenyl)-1-phenyl-1H-pyrazol-4-yl)-1-phenylprop-2-en-1-one conjugates 5a–r were designed; synthesized; characterized by 1H, 13C NMR, and ESI-MS; and evaluated for tubulin polymerization inhibitory activity and in vitro cytotoxicity against breast (MCF-7), cervical (SiHa), and prostate (PC-3) cancer cell lines, as well as a normal cell line (HEK-293T). The compounds were also tested to determine their binding modes at the colchicine-binding site of tubulin protein (PDB ID-3E22), for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…69,70 According to previously published research, the lead compound showed the most effective inhibition of tubulin polymerization with an IC 50 value of 1.15 ± 0.06 M. It also significantly interacted with the Lys352 residue via a π−cation interaction in addition to Hbonds with other residues within the colchicine binding site of tubulin. 71 The ligand 6h displayed a π−cationic interaction with the residue Lys352 and showed the most promising anticancer activity in the current investigation.…”
Section: Molecular Docking Studiesmentioning
confidence: 76%
See 1 more Smart Citation
“…69,70 According to previously published research, the lead compound showed the most effective inhibition of tubulin polymerization with an IC 50 value of 1.15 ± 0.06 M. It also significantly interacted with the Lys352 residue via a π−cation interaction in addition to Hbonds with other residues within the colchicine binding site of tubulin. 71 The ligand 6h displayed a π−cationic interaction with the residue Lys352 and showed the most promising anticancer activity in the current investigation.…”
Section: Molecular Docking Studiesmentioning
confidence: 76%
“…The π–cationic interaction with the residue Lys352 plays an important role in many approved anticancer drugs. For instance, sorafenib, a drug approved to treat liver cancer, interacts with a positively charged lysine residue of human p38 MAP kinase, and lapatinib, a drug approved to treat breast cancer, interacts with a positively charged lysine residue of ErbB4 kinase through π–cationic interaction. , According to previously published research, the lead compound showed the most effective inhibition of tubulin polymerization with an IC 50 value of 1.15 ± 0.06 M. It also significantly interacted with the Lys352 residue via a π–cation interaction in addition to H-bonds with other residues within the colchicine binding site of tubulin . The ligand 6h displayed a π–cationic interaction with the residue Lys352 and showed the most promising anticancer activity in the current investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Also, in silico ADME predictions were found to be favourable with good drug likeness character-istics to encourage the in vitro as well as docking-based anticancer results. [68] To improve the therapeutic efficacy of curcuminoids (2 a-j), some new pyrazole tethered curcuminoids (2 k-t, Figure 6) were synthesized and evaluated for anticancer action against selected cancer cell by Pham and co-workers (2020). After initial structural characterization, all synthesized molecules were tested in vitro for their anticancer effect on HepG2 cancer cell lines while Ellipticine was taken as reference anticancer agent throughout the study.…”
Section: Natural Pyrazole and Its Bio-isosteric Hybrids As Anticancer...mentioning
confidence: 99%
“…Chalcone‐pyrazole hybrids 11 (Figure 3; IC 50 : 2.13–42.70 µM, MTT assay) showed moderate to excellent antiproliferative activity against MCF‐7 cancer cells, and the SAR elucidated that bis‐methoxy group on the phenyl ring was beneficial for the activity. [ 28 ] Particularly, hybrids 11a,b (IC 50 : 2.13 and 3.45 µM, respectively) not only were superior to combretastatin A‐4 (IC 50 : 4.12 µM) against MCF‐7 cancer cells, but also were nontoxic (IC 50 : >50 µM) against HEK‐293 cells. In addition, hybrids 11a,b (IC 50 : 1.15 and 1.95 µM) also showed significant inhibition of tubulin polymerization, and the activity was not inferior to that of combretastatin A‐4 (IC 50 : 1.46 µM).…”
Section: Chalcone‐azole Hybridsmentioning
confidence: 99%